Negative electrode material and preparation method thereof and all-solid-state lithium battery
By designing the gap between the core and the shell in the negative electrode material of the all-solid-state lithium battery and introducing a carbon material layer into the core and the shell, the problems of low conductivity and large volume changes in the existing silicon negative electrode materials are solved, and an all-solid-state lithium battery with high capacity and good circulation performance are achieved.
Patent Information
- Application Number
- CN202110300911.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-03-19
AI Technical Summary
The existing silicon negative electrode materials have low conductivity and large volume changes in all solid state lithium batteries, resulting in poor capacity attenuation and cycle performance.
A negative electrode material is designed, including a gap between the core and the shell, which consists of lithium silicon alloy particles and a first carbon material layer, and the shell consists of lithium silicon alloy layer and a second carbon material layer. Through this structure, the electron conductivity is improved and the volume expansion effect is reduced.
It achieves high electronic conductivity, low volume expansion effect and good cycle stability, and improves the capacity and circulation performance of all solid-state lithium batteries.
Smart Images

Figure CN115117309B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to negative electrode materials and preparation methods thereof and all-solid-state lithium batteries. Background Art
[0002] In recent years, all-solid-state lithium batteries using solid electrolytes have received widespread attention due to their high safety. Among them, silicon anodes with high theoretical specific capacity and high safety are considered to be an effective way to break through the energy density of all-solid-state lithium batteries. However, the existing silicon anode materials have low conductivity and cannot be used directly as anodes. At the same time, they are prone to huge volume changes during the process of lithium extraction / insertion, which leads to rapid capacity decay of all-solid-state lithium batteries and poor cycle performance, limiting the application of all-solid-state lithium batteries. Summary of the invention
[0003] In view of this, the present application provides a negative electrode material, a preparation method thereof, and an all-solid-state lithium battery. The negative electrode material has high electronic conductivity, small volume expansion effect, good cycle stability, and excellent electrochemical performance. The all-solid-state lithium battery made from the negative electrode material has high capacity and good cycle performance, which is conducive to its application.
[0004] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising a core and a shell arranged outside the core, a gap being formed between the core and the shell, the core comprising lithium silicon alloy particles and a first carbon material layer arranged on the surface of the lithium silicon alloy particles, the shell comprising a lithium silicon alloy layer and a second carbon material layer, the second carbon material layer being arranged between the lithium silicon alloy layer and the core, the lithium silicon alloy particles being made of Li x Si, the material of the lithium silicon alloy layer is Li y Si, wherein 0<x<4.4, 0<y≤4.4.
[0005] Optionally, the mass ratio of the lithium-silicon alloy particles to the lithium-silicon alloy layer is 0.1-100.
[0006] Optionally, the total mass of the first carbon material layer and the second carbon material layer accounts for 1%-30% of the mass of the negative electrode material.
[0007] Optionally, the volume of the voids accounts for 10%-75% of the sum of the volumes of the voids and the inner core.
[0008] Optionally, the particle size of the lithium silicon alloy particles is 20 nm-1 μm.
[0009] Optionally, the thickness of the lithium-silicon alloy layer is 10 nm-1 μm.
[0010] Optionally, the materials of the first carbon material layer and the second carbon material layer are respectively selected from at least one of graphite, carbon black, graphene, carbon fiber, carbon nanotube and cracked carbon.
[0011] In the negative electrode material provided in the first aspect of the present application, by setting a gap between the inner core and the outer shell, the volume change of the negative electrode material can be effectively coped with, the structural morphology can be maintained during the cycle, and the cycle stability can be enhanced; at the same time, the first carbon material layer and the second carbon material layer can be set to improve the electronic conductivity of the negative electrode material and enhance the electrochemical performance of the negative electrode material.
[0012] In a second aspect, the present application also provides a method for preparing a negative electrode material, comprising:
[0013] In Li z The surface of Si particles is coated with carbon material to obtain a first coating, wherein 0<z≤4.4;
[0014] Coating a silicon material on the surface of the first coating to obtain a second coating;
[0015] The second coating is heated to obtain a negative electrode material, wherein the negative electrode material includes a core and a shell arranged outside the core, a gap is formed between the core and the shell, the core includes lithium silicon alloy particles and a first carbon material layer arranged on the surface of the lithium silicon alloy particles, the shell includes a lithium silicon alloy layer and a second carbon material layer, the second carbon material layer is arranged between the lithium silicon alloy layer and the core, and the material of the lithium silicon alloy particles is Li x Si, the material of the lithium silicon alloy layer is Li y Si, wherein 0<x<4.4, 0<y≤4.4, x<z.
[0016] Optionally, the heating includes treating at 100°C-250°C for 10 min-8 h.
[0017] The preparation method of the negative electrode material provided in the second aspect of the present application is simple, easy to operate, suitable for industrial production, and is conducive to the application of the negative electrode material.
[0018] In a third aspect, the present application also provides an all-solid-state lithium battery, comprising a positive electrode, a negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the negative electrode comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.
[0019] Optionally, the negative electrode includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, and the negative electrode material layer includes the negative electrode material.
[0020] Furthermore, the negative electrode material layer does not contain solid electrolyte material and conductive agent.
[0021] The all-solid-state lithium battery provided in the third aspect of the present application has good cycle performance and excellent electrochemical performance, which is conducive to its application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the implementation modes of the present application, the drawings required for use in the implementation modes of the present application will be described below.
[0023] Figure 1 A schematic diagram of the structure of a negative electrode material provided in one embodiment of the present application.
[0024] Figure 2 A schematic diagram of a process for preparing a negative electrode material provided in one embodiment of the present application.
[0025] Figure 3 A schematic diagram of the structure of an all-solid-state lithium battery provided in one embodiment of the present application.
[0026] Description of labels:
[0027] Core-11, lithium silicon alloy particles-111, first carbon material layer-112, shell-12, lithium silicon alloy layer-121, second carbon material layer-122, gap-13, negative electrode material-10, negative electrode material layer-101, negative electrode current collector-102, negative electrode-100, positive electrode material layer-201, positive electrode current collector-202, positive electrode-200, solid electrolyte layer-300. DETAILED DESCRIPTION
[0028] The following are preferred implementations of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
[0029] The disclosure below provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the disclosure of the present application, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the various specific processes and material examples provided by the present application, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.
[0030] See also Figure 1, is a schematic diagram of the structure of a negative electrode material provided in one embodiment of the present application, wherein the negative electrode material 10 comprises a core 11 and a shell 12 disposed outside the core 11, wherein a gap 13 is provided between the core 11 and the shell 12, wherein the core 11 comprises a lithium silicon alloy particle 111 and a first carbon material layer 112 disposed on the surface of the lithium silicon alloy particle 111, wherein the shell 12 comprises a lithium silicon alloy layer 121 and a second carbon material layer 122, wherein the second carbon material layer 122 is disposed between the lithium silicon alloy layer 121 and the core 11, and the material of the lithium silicon alloy particle 111 is Li x Si, the material of the lithium silicon alloy layer 121 is Li y Si, wherein 0<x<4.4, 0<y≤4.4.
[0031] In the present application, the negative electrode material 10 has a yolk-shell structure, and there is a gap 13 between the outer shell 12 and the inner core 11, so as to effectively suppress the volume expansion effect of the negative electrode material 10 during use, maintain the long-term stability of the morphology of the negative electrode material 10, and thus enhance the cycle performance; at the same time, the negative electrode material 10 has a first carbon material layer 112 and a second carbon material layer 122, which improves the electronic conductivity of the negative electrode material 10, and there is no need to use additional solid electrolytes and conductive agents during use, thereby improving the specific capacity of the negative electrode and thus improving the electrochemical performance.
[0032] In the present application, the material of the lithium silicon alloy particles 111 is Li x Si, the material of the lithium silicon alloy layer 121 is Li y Si, x and y may be the same or different. In one embodiment of the present application, 2<x<4.4, 2<y≤4.4. Specifically, x and y are independently selected from 1.71, 2.33, 3.25 or 3.75.
[0033] In the present application, the shape of the lithium silicon alloy particles 111 is not limited, and specifically can be but not limited to spherical, quasi-spherical, etc. In the embodiment of the present application, the particle size of the lithium silicon alloy particles 111 is 20nm-1μm. It can be understood that when the material is quasi-spherical, the particle size is an equivalent particle size. Further, the particle size of the lithium silicon alloy particles 111 is 50nm-900nm. Further, the particle size of the lithium silicon alloy particles 111 is 100nm-850nm. Specifically, the particle size of the lithium silicon alloy particles 111 can be but not limited to 10nm, 80nm, 150nm, 200nm, 300nm, 500nm, 650nm, 700nm, 820nm, 900nm or 970nm, etc. By setting the lithium silicon alloy particles 111 of the above particle size, the volume expansion effect of the lithium silicon alloy can be alleviated and the cycle performance of the negative electrode material 10 can be enhanced.
[0034] In the embodiment of the present application, the mass fraction of the lithium silicon alloy particles 111 in the negative electrode material 10 is 50%-85%. Further, the mass fraction of the lithium silicon alloy particles 111 in the negative electrode material 10 is 55%-80%. Further, the mass fraction of the lithium silicon alloy particles 111 in the negative electrode material 10 is 60%-75%. Specifically, the mass fraction of the lithium silicon alloy particles 111 in the negative electrode material 10 can be, but not limited to, 55%, 58%, 62%, 65%, 69%, 70%, 75%, 76%, 80% or 84%, etc. By setting the above-mentioned mass proportion of lithium silicon alloy particles 111, the specific capacity of the negative electrode material 10 is guaranteed, which is conducive to its application in all-solid-state lithium batteries.
[0035] In an embodiment of the present application, the thickness of the lithium silicon alloy layer 121 is 10nm-1μm. Further, the thickness of the lithium silicon alloy layer 121 is 50nm-950nm. Furthermore, the thickness of the lithium silicon alloy layer 121 is 150nm-800nm. Specifically, the thickness of the lithium silicon alloy layer 121 can be, but is not limited to, 10nm, 80nm, 100nm, 150nm, 200nm, 300nm, 500nm, 650nm, 700nm, 820nm, 900nm or 980nm, etc. By setting the lithium silicon alloy layer 121 of the above thickness, as the skeleton of the negative electrode material 10, it plays a role in supporting and coating the lithium silicon alloy particles 111 in the negative electrode material 10, which is beneficial to improve the cycle performance of the negative electrode material 10.
[0036] In an embodiment of the present application, the mass ratio of the lithium silicon alloy particles 111 to the lithium silicon alloy layer 121 is 0.1-100. Further, the mass ratio of the lithium silicon alloy particles 111 to the lithium silicon alloy layer 121 is 1-95. Furthermore, the mass ratio of the lithium silicon alloy particles 111 to the lithium silicon alloy layer 121 is 10-90. Specifically, the mass ratio of the lithium silicon alloy particles 111 to the lithium silicon alloy layer 121 can be, but is not limited to, 0.5, 1.5, 15, 20, 30, 37, 45, 50, 55, 60, 75, 80 or 92, etc. Through the mass ratio of the lithium silicon alloy particles 111 and the lithium silicon alloy layer 121, the lithium silicon alloy layer 121 can mainly play the role of protecting and supporting the lithium silicon alloy particles 111, and at the same time it is beneficial to improve the specific capacity of the negative electrode material 10.
[0037] In the present application, there is a gap 13 between the core 11 and the shell 12. The space formed by the gap 13 is conducive to alleviating the volume expansion effect of the lithium silicon alloy particles 111 during use, thereby ensuring the structural stability of the negative electrode material 10 during use.
[0038] In the embodiment of the present application, the volume of the void 13 accounts for 15%-70% of the total volume of the void 13 and the core 11. Further, the volume of the void 13 accounts for 20%-60% of the total volume of the void 13 and the core 11. Further, the volume of the void 13 accounts for 25%-50% of the total volume of the void 13 and the core 11. Specifically, the volume of the void 13 may be, but is not limited to, 15%, 20%, 28%, 30%, 35%, 40%, 47%, 50%, 55%, 60% or 69% of the total volume of the void 13 and the core 11. By setting the void 13 with the above volume proportion, it is more conducive to alleviating the volume expansion effect generated by the lithium silicon alloy particles 111.
[0039] In the present application, the electronic conductivity of the negative electrode material 10 is improved by providing the first carbon material layer 112 and the second carbon material layer 122. In the embodiment of the present application, the materials of the first carbon material layer 112 and the second carbon material layer 122 are respectively selected from at least one of graphite, carbon black, graphene, carbon fiber, carbon nanotubes and cracked carbon. Further, the materials of the first carbon material layer 112 and the second carbon material layer 122 are the same.
[0040] In the embodiment of the present application, the total mass of the first carbon material layer 112 and the second carbon material layer 122 accounts for 1%-30% of the mass of the negative electrode material 10. Further, the total mass of the first carbon material layer 112 and the second carbon material layer 122 accounts for 5%-25% of the mass of the negative electrode material 10. Further, the total mass of the first carbon material layer 112 and the second carbon material layer 122 accounts for 10%-20% of the mass of the negative electrode material 10. Specifically, the total mass of the first carbon material layer 112 and the second carbon material layer 122 accounts for but is not limited to 1%, 3%, 5%, 10%, 15%, 18%, 20%, 22%, 25%, 27%, 29% or 30% of the mass of the negative electrode material 10. Setting the first carbon material layer 112 and the second carbon material layer 122 with the above mass proportion is more conducive to improving the electronic conductivity of the negative electrode material 10, and at the same time the content will not be too large, so as to ensure the specific capacity of the negative electrode material 10.
[0041] In the embodiment of the present application, the first carbon material layer 112 completely or incompletely covers the surface of the lithium-silicon alloy particle 111 ; the second carbon material layer 122 completely or incompletely covers the inner surface of the lithium-silicon alloy layer 121 .
[0042] In the embodiment of the present application, the ionic conductivity of the negative electrode material 10 at room temperature is 10 -7 S cm -1 Above, the room temperature is 15℃-30℃.
[0043] In the embodiment of the present application, the electronic conductivity of the negative electrode material 10 at room temperature is 10 -2 S cm -1Above, the room temperature is 15℃-30℃.
[0044] See also Figure 2 , is a schematic flow chart of a method for preparing a negative electrode material provided in one embodiment of the present application, comprising:
[0045] S101: In Li z The surface of Si particles is coated with carbon material to obtain a first coating, wherein 0<z≤4.4.
[0046] S102: Coating the surface of the first coating with silicon material to obtain a second coating.
[0047] S103: heating the second coating to obtain a negative electrode material, wherein the negative electrode material comprises a core and a shell disposed outside the core, wherein a gap is formed between the core and the shell, wherein the core comprises lithium-silicon alloy particles and a first carbon material layer disposed on the surface of the lithium-silicon alloy particles, wherein the shell comprises a lithium-silicon alloy layer and a second carbon material layer, wherein the second carbon material layer is disposed between the lithium-silicon alloy layer and the core, and wherein the material of the lithium-silicon alloy particles is Li x Si, the material of the lithium silicon alloy layer is Li y Si, wherein 0<x<4.4, 0<y≤4.4, x<z.
[0048] In this application, in Li z The surface of Si particles is coated with carbon material, 0<z≤4.4. In the embodiment of the present application, z is 2<z≤4.4. Specifically, Li z Si may include Li 1.71 Si、Li 2.33 Si、Li 3.25 Si、Li 3.75 Si、Li 4.4 At least one of Si, etc.
[0049] In the implementation mode of the present application, in Li z The surface coating of Si particles with carbon materials can be performed by a ball mill or a solid-solid coating device. In one embodiment of the present application, the ball milling method can be wet ball milling or dry ball milling. Specifically, the solvent in the wet ball milling can be but is not limited to at least one selected from toluene, xylene, anisole, heptane, decane, ethyl acetate, ethyl propionate, butyl butyrate, N-methylpyrrolidone and acetone. In one embodiment of the present application, Li z After Si particles and carbon materials are mixed and ball-milled, a first coating is obtained. Further, the ball-milling speed is 50 rpm-250 rpm, and the time is 5 min-30 min. In another embodiment of the present application, Li zThe Si particles and the carbon material are placed in a solid-solid coating device and mixed to obtain a first coating. Furthermore, the rotation speed of the solid-solid coating device is 1000 rpm-8000 rpm, and the time is 3 min-10 min.
[0050] In an embodiment of the present application, the carbon material includes at least one of graphite, carbon black, graphene, carbon fiber, carbon nanotube and cracked carbon.
[0051] In an embodiment of the present application, the silicon material can be coated on the surface of the first coating by vapor deposition. Specifically, the vapor deposition method can be, but is not limited to, magnetron sputtering, vacuum evaporation, atmospheric pressure chemical vapor deposition, low pressure chemical vapor deposition, etc. It can be understood that there is no gap between the silicon material layer in the second coating and the first coating. In an embodiment of the present application, the silicon material is elemental silicon.
[0052] In the present application, the second coating is heated to make the Li z The lithium in the Si particles is removed and reacts with the silicon material to form a lithium-silicon alloy layer 121. At the same time, due to the removal of lithium, Li z The volume of Si particles decreases, so that the generated lithium-silicon alloy layer 121 is closer to the smaller Li z Gaps 13 are created between Si particles. At the same time, the carbon material layer separates, partly on the inner surface of the lithium-silicon alloy layer 121 and partly on the smaller Li z The outer surface of the Si particles, and then after heating, the volume of the Li z Si particles become lithium silicon alloy particles 111; the silicon material layer becomes a lithium silicon alloy layer 121; the carbon material layer becomes a first carbon material layer 112 and a second carbon material layer 122. In an embodiment of the present application, the first carbon material layer 112 completely or incompletely covers the surface of the lithium silicon alloy particles 111, and the second carbon material layer 122 completely or incompletely covers the inner surface of the lithium silicon alloy layer 121. In an embodiment of the present application, the first carbon material layer 112 and the second carbon material layer 122 are made of the same material. Furthermore, when the carbon material includes two or more materials, the proportion of each material in the first carbon material layer 112 and the second carbon material layer 122 may be the same or different. Specifically, for example, the carbon material is selected from graphite and carbon black, and the materials of the first carbon material layer 112 and the second carbon material layer 122 finally formed include graphite and carbon black, and the proportions of graphite and carbon black in the first carbon material layer 112 and the second carbon material layer 122 may be the same or different.
[0053] In one embodiment of the present application, heating includes treating at 100°C-250°C for 10min-8h. Further, heating includes treating at 100°C-250°C for 20min-6h. Still further, heating includes treating at 150°C-220°C for 20min-4h. Specifically, the heating temperature may be but is not limited to 100°C, 120°C, 150°C, 180°C, 200°C, 230°C or 240°C, and the heating time may be but is not limited to 10min, 15min, 30min, 1h, 1.5h, 2h, 3h, 4.5h, 5.5h or 7h, etc. Under the above heating conditions, Li z The lithium in the Si particles can be easily released to react with the silicon material, while also ensuring that the Li z The lithium in the Si particles will not be completely removed, ensuring that the lithium silicon alloy particles 111 and the voids 13 of appropriate size are obtained. Furthermore, the heating also includes heating to 100°C-250°C at a rate of 1°C / min-10°C / min. Specifically, it can be but not limited to 1°C / min, 3°C / min, 5°C / min, 8°C / min or 10°C / min. Furthermore, after heating, the temperature is lowered at a rate of 1°C / min-10°C / min. Specifically, it can be but not limited to 2°C / min, 4°C / min, 5°C / min, 8.5°C / min or 10°C / min.
[0054] In the embodiment of the present application, the preparation of the negative electrode material 10 is carried out under a protective gas. Specifically, the protective gas includes at least one of nitrogen, helium, hydrogen, etc.
[0055] The relevant parameters and functions of the negative electrode material 10 prepared by the preparation method of the present application are as described above and will not be repeated here.
[0056] The preparation method of the negative electrode material 10 provided in the present application is simple, easy to operate, suitable for industrial production, and is conducive to the application of the negative electrode material 10.
[0057] See also Figure 3 , is a schematic structural diagram of an all-solid-state lithium battery provided in one embodiment of the present application, the all-solid-state lithium battery includes a positive electrode 200, a negative electrode 100 and a solid electrolyte layer 300 located between the positive electrode 200 and the negative electrode 100, and the negative electrode 100 includes the negative electrode material 10 in any of the above embodiments.
[0058] In the embodiment of the present application, the negative electrode 100 includes a negative electrode current collector 102 and a negative electrode material layer 101 disposed on the negative electrode current collector 102, and the negative electrode material layer 101 includes a negative electrode material 10. Specifically, the thickness of the negative electrode material layer 101 may be, but is not limited to, 5 μm-50 μm.
[0059] In the embodiment of the present application, the negative electrode material layer 101 does not contain solid electrolyte material and conductive agent. In this way, the negative electrode material layer 101 can include a large amount of negative electrode material 10 with electrochemical activity, thereby making the capacity of the negative electrode 100 larger and the energy density of the all-solid-state lithium battery higher.
[0060] In an embodiment of the present application, the negative electrode material layer 101 also includes at least one of the binders. Among them, the binder helps to firmly fix the negative electrode material layer 101 on the negative electrode current collector 102 and make the negative electrode material layer 101 have a certain elasticity. In an embodiment of the present application, the binder may include but is not limited to polythiophene, polypyrrole, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polystyrene, polyacrylamide, ethylene-propylene-diene copolymer resin, styrene butadiene rubber, polybutadiene, fluororubber, polyvinyl pyrrolidone, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, carboxypropyl cellulose, ethyl cellulose, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene rubber. In another embodiment of the present application, the mass percentage of the binder in the negative electrode material layer 101 is 0.5%-5%. Specifically, the mass percentage of the binder in the negative electrode material layer 101 may be, but is not limited to, 1%-5%, 1.5%-4.5%, 2%-4% or 2.5%-3.8%.
[0061] In the embodiment of the present application, the positive electrode 200 may include a positive electrode current collector 202 and a positive electrode material layer 201 disposed on the positive electrode current collector 202. The positive electrode material layer 201 may include a positive electrode active material, a conductive agent, a positive electrode solid electrolyte material, and a positive electrode binder.
[0062] In the embodiment of the present application, the positive electrode active material includes one or more of oxide type, sulfide type, polyanion type and composites of the above materials. In one embodiment of the present application, the oxide type positive electrode active material may include but is not limited to TiO2, Cr3O8, V2O5, MnO2, NiO, WO3, LiMn2O4, Li2CuO2, LiCo m Ni 1-m O2(0≤m≤1), LiCo a Ni 1-a-b Al b O2(0≤a≤1,0≤b≤1), LiFe c Mn d G e O4 (G is selected from at least one of Al, Mg, Ga, Cr, Co, Ni, Cu, Zn and Mo, 0≤c≤1, 0≤d≤1, 0≤e≤1, c+d+e=1), Li 1+f L 1-g-h H g Rh O2 (L, H and R are independently selected from at least one of Li, Co, Mn, Ni, Fe, Al, Mg, Ga, Ti, Cr, Cu, Zn, Mo, F, I, S and B, and L, H and R are different elements, and -0.1≤f≤0.2, 0≤g≤1, 0≤h≤1, 0≤g+h≤1) etc. Specifically, the oxide-type positive electrode active material may be, but is not limited to, one or more of LiCoO2, LiNiO2, LiMn2O4. In another embodiment of the present application, the sulfide-type positive electrode active material may include TiS2, V2S3, FeS, FeS2, WS2, LiJS i (J is selected from at least one of Ti, Fe, Ni, Cu and Mo, 1≤i≤2.5), etc. In another embodiment of the present application, the polyanionic positive electrode active material may specifically include at least one of LiFePO4, Li3V2(PO4)3, Li3V3(PO4)3 and LiVPO4F.
[0063] In the embodiment of the present application, the particle size of the positive electrode active material is 100 nm-500 μm. Specifically, the particle size of the positive electrode active material may be, but is not limited to, 100 nm-100 μm, 100 nm-50 μm or 500 nm-50 μm.
[0064] In the embodiment of the present application, the surface of the positive electrode active material may also have a coating layer to optimize the interface between the positive electrode material layer 201 and the solid electrolyte, reduce the interface impedance, and improve the cycle stability. Specifically, the coating layer on the surface of the positive electrode active material may be LiNbO3, LiTaO3, Li3PO4, Li4Ti5O 12 In a specific embodiment, 1000 g of LiCoO2, 51 mL of niobium ethoxide, 12 g of lithium ethoxide, 1000 mL of deionized water and 1000 mL of ethanol are fully mixed, and under continuous stirring, ammonia water is added dropwise to adjust the pH to 10, the solution is evaporated to dryness, and the obtained powder is heated at 400° C. for 8 h to obtain a LiCoO2 positive electrode active material coated with LiNbO3 on the surface.
[0065] In the present application, there is no particular restriction on the positive electrode binder in the positive electrode material layer 201, for example, it can be at least one of fluorine-containing resin, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyolefin, styrene-butadiene rubber, etc. There is no particular restriction on the conductive agent in the positive electrode material layer 201, and conventional materials available in the art can be used, such as at least one of conductive carbon black (such as acetylene black, Ketjen black), carbon nanotubes, carbon fibers and graphite. In one embodiment of the present application, the mass percentage content of the positive electrode binder in the positive electrode material layer 201 is 0.01%-10%. Specifically, the mass percentage content of the positive electrode binder in the positive electrode material layer 201 can be, but not limited to, 0.015%-8%, 0.02%-7%, 0.02%-5% or 0.05%-4.5%, etc. In another embodiment of the present application, the conductive agent can be, but not limited to, at least one of acetylene black, carbon nanowires, graphite and graphene. In another embodiment of the present application, the mass percentage of the conductive agent in the positive electrode material layer 201 is 0.1%-20%. Specifically, the mass percentage of the conductive agent in the positive electrode material layer 201 can be, but is not limited to, 0.5%-18%, 1%-15%, 1%-10% or 3%-8.5%, etc.
[0066] In the embodiment of the present application, the negative electrode current collector 102 and the positive electrode current collector 202 are independently selected from metal foil or alloy foil. Among them, the metal foil includes copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold or silver foil, and the alloy foil includes stainless steel, or an alloy containing at least one element of copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold and silver. For example, the negative electrode current collector 102 can be specifically aluminum foil, and the positive electrode current collector 202 can be specifically copper foil. The thickness and surface roughness of the negative electrode current collector 102 and the positive electrode current collector 202 in the present application can be adjusted according to actual needs.
[0067] In an embodiment of the present application, the solid electrolyte layer 300 can be formed by coating and drying a slurry containing a solid electrolyte material and a solvent, and the components of the solid electrolyte layer 300 include a solid electrolyte material. In another embodiment of the present application, the solid electrolyte layer 300 may also contain a binder, and its material may be selected from the binder in the above-mentioned negative electrode material layer 101, which will not be repeated here. In one embodiment of the present application, the solid electrolyte layer 300 can be combined with the negative electrode material layer 101 by coating, and then the solid electrolyte layer 300 can be combined with the positive electrode 200 with the positive electrode material layer 201 by pressing.
[0068] In an embodiment of the present application, the solid electrolyte material for the positive electrode and the solid electrolyte material in the solid electrolyte layer 300 are independently selected from at least one of a garnet-type solid electrolyte and a sulfur-based solid electrolyte. The material of the solid electrolyte layer 300 is the same as or different from the solid electrolyte material for the positive electrode. For example, the composition of the solid electrolyte layer selects a reduction-resistant solid electrolyte material to protect the negative electrode material 10 of the negative electrode and further improve the cycle stability of the negative electrode material 10. Furthermore, when preparing the solid electrolyte layer 300 and the positive electrode material layer 201, the particle size of the solid electrolyte material used can be 100nm-5μm. In one embodiment of the present application, the chemical formula of the garnet-type solid electrolyte is Li 7+p-q-3u Al u La 3-p X p Zr 2- q Y q O 12 , wherein 0<p≤1, 0<q≤1, 0<u≤1, X is selected from at least one of La, Ca, Sr, Ba and K, and Y is selected from at least one of Ta, Nb, W and Hf. In another embodiment of the present application, the sulfur-based solid electrolyte includes crystalline Li r Q s P t1 S z , glassy Li2S-P2S5 and glass-ceramic Li2S-P2S5 and their dopants, wherein the crystalline Li r Q s P t1 S z In which Q is selected from one or more of Si, Ge and Sn, r+4s+5t1=2z, 0≤s≤1.5. Glassy Li2S-P2S5 includes different products composed of Li2S and P2S5, such as Li7P3S 11 Or 70Li2S-30P2S5, etc.
[0069] In an embodiment of the present application, a method for preparing an all-solid-state lithium battery is also provided, comprising:
[0070] S201: preparing the negative electrode 100: the negative electrode material 10 is mixed with the first solvent, and at least one of the binders is added to obtain a negative electrode mixed slurry; the negative electrode mixed slurry is coated on the negative electrode current collector 102, and after drying and pressing treatment, the negative electrode 100 is obtained.
[0071] S202: preparing a solid electrolyte layer 300: in the presence of a protective gas, the solid electrolyte material and the second solvent are evenly mixed to obtain a solid electrolyte mixed slurry, the solid electrolyte mixed slurry is continuously coated on the negative electrode, and after drying, a solid electrolyte layer 300 is formed on the negative electrode 100.
[0072] S203: preparing positive electrode 200: mixing positive electrode active material, positive electrode solid electrolyte, conductive agent, positive electrode binder and third solvent evenly to obtain positive electrode mixed slurry; coating the positive electrode mixed slurry on positive electrode collector 202, drying and pressing to obtain positive electrode 200.
[0073] S204: In the presence of a protective gas, align the negative electrode 100 with the solid electrolyte layer 300 with the prepared positive electrode 200, fit the tabs, and obtain an all-solid-state lithium battery after hot pressing, vacuum sealing and isostatic pressing.
[0074] In the embodiment of the present application, the first solvent, the second solvent and the third solvent are independently selected from at least one of water, ethanol, toluene, xylene, anisole, acetonitrile, heptane, decane, ethyl acetate, ethyl propionate, butyl butyrate, N-methylpyrrolidone, acetone, etc. The amount of each solvent can generally be 50wt%-400wt% of the mass of dry materials in the corresponding mixed slurry.
[0075] In the embodiment of the present application, the tabletting may be, but is not limited to, roller pressed at 0-5 MPa.
[0076] In the embodiment of the present application, the temperature of the hot pressing treatment may be but is not limited to about 100°C, and the hot pressing treatment time may be but is not limited to 0.5h-3h; the isostatic pressing pressure may be but is not limited to above 100MPa, for example, the pressure is 100MPa-300MPa; the isostatic pressing treatment time may be but is not limited to 3min-10min.
[0077] The all-solid-state lithium battery provided in the present application, because it contains the above-mentioned negative electrode material 10, has high battery capacity and good cycle performance, which is conducive to its application.
[0078] The present application is further described below with reference to a number of embodiments.
[0079] Example 1
[0080] A method for preparing an all-solid-state lithium battery comprises:
[0081] (1) Preparation of negative electrode
[0082] Under argon atmosphere, 1000 g Li 4.4 Si material (particle size is about 50nm) and 200g of graphite are placed in a solid-solid coating device and run at a speed of 3000rpm for 10min to obtain the first coating, which is graphite-coated Li 4.4Si. 1000g of the first coating was placed on the sample stage of the magnetron sputtering equipment. The sample stage had a stirring and flipping function. Si was used as the target source. The system was evacuated to an absolute pressure of less than 0.001Pa. At 100°C, the stirring function of the sample stage was turned on. The magnetron sputtering power supply was turned on. Si was deposited on the first coating on the sample stage at a sputtering power of 250W for 100 hours to obtain a second coating. The second coating was Si-coated first coating. Under an argon atmosphere, the second coating was placed in an electric heating furnace, heated to 200°C at a rate of 5°C / min, and maintained for 30 minutes. The temperature was rapidly cooled to room temperature at a rate of 10°C / min to obtain a negative electrode material. The negative electrode material included a core and a shell. There was a gap between the core and the shell. The core included lithium-silicon alloy particles and a first graphite layer arranged on the surface of the lithium-silicon alloy particles. The shell included a lithium-silicon alloy layer and a second graphite layer arranged on the inner surface of the lithium-silicon alloy layer. The scanning electron microscope (SEM) results of the samples cut by focused ion beam (FIB) showed that the particle size of the lithium silicon alloy particles in the negative electrode material was about 50nm, the thickness of the lithium silicon alloy layer was 50nm, and the average particle size of the negative electrode material was about 150nm.
[0083] Under argon atmosphere, 1000g of negative electrode material, 30g of binder SBR, and 1500mL of toluene solution were placed in a disperser for 30 minutes to form a stable and uniform negative electrode slurry. The negative electrode slurry was uniformly and intermittently coated on a copper foil (width 160mm, thickness 16μm), then dried at 373K, and pressed by a roller press to obtain a negative electrode.
[0084] (2) Fabrication of solid electrolyte layer
[0085] Under an argon atmosphere, 600 g of 70Li2S·30P2S5 glassy solid electrolyte material was placed in 1200 g of toluene solution containing 30 g of butadiene rubber binder, and heated and stirred until a stable and uniform slurry was obtained; the slurry was continuously coated on the negative electrode obtained in step (1), and then dried at 373K to form a solid electrolyte layer with a thickness of 50 μm on the negative electrode.
[0086] (3) Preparation of positive electrode
[0087] 1000 g LiCoO2, 51 mL niobium ethoxide, 12 g lithium ethoxide, 1000 mL deionized water and 1000 mL ethanol were fully mixed. Under continuous stirring, ammonia water was added dropwise to adjust the pH to 10. The solution was evaporated to dryness and the obtained powder was heated at 400 °C for 8 h to obtain a LiCoO2 positive electrode active material coated with LiNbO3 on the surface.
[0088] Take 1000g of the above-mentioned LiCoO2 positive electrode active material coated with LiNbO3, 150g of Li10 GeP2S 12 Solid electrolyte material, 30g of binder butadiene rubber, 20g of acetylene black, and 20g of carbon fiber are added to 1500g of toluene solution, and then stirred in a vacuum mixer to form a stable and uniform positive electrode mixed slurry; the positive electrode mixed slurry is uniformly and intermittently coated on an aluminum foil (width 160mm, thickness 16μm), and then dried at 393K. After being pressed by a roller press, a positive electrode material layer with a thickness of 100μm is formed on the aluminum foil to obtain a positive electrode.
[0089] (4) Fabrication of all-solid-state lithium batteries
[0090] Under a protective atmosphere, the positive electrode and the negative electrode with a solid electrolyte layer were aligned and placed in a tablet press, the tabs were fitted, hot pressed at 100°C for 1 hour, vacuum sealed with an aluminum-plastic film, and finally pressed at 200 MPa for 300 seconds in an isostatic press to obtain an all-solid-state lithium battery.
[0091] Example 2
[0092] A preparation of an all-solid-state lithium battery, which is substantially the same as Example 1, except that Li 4.4 The Si material was changed to 10nm, 200g of graphite was changed to 400g of graphite, and the magnetron sputtering time was changed from 100h to 25h.
[0093] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided:
[0094] Comparative Example 1
[0095] A preparation of an all-solid-state lithium battery, which is different from Example 1 in that a carbon-coated silicon negative electrode material is used to replace the negative electrode material, wherein the preparation method of the carbon-coated silicon negative electrode material comprises: placing 1000g of Si and 240g of sucrose in 1000mL of deionized water and stirring evenly, then heating to 100°C during stirring, taking out the solid after the water evaporates, and heating to 300°C in an inert atmosphere to obtain a carbon-coated silicon negative electrode material. The carbon-coated silicon negative electrode material is directly used as the negative electrode, and the other steps remain unchanged.
[0096] Comparative Example 2
[0097] A preparation of an all-solid-state lithium battery, which differs from Example 1 in that the specific operation of step (1) is as follows: 1000 g of Si and 240 g of sucrose are placed in 1000 mL of deionized water and stirred evenly, then heated to 100° C. during stirring, and after the water evaporates, the solid is taken out and heated to 300° C. under an inert atmosphere to obtain a carbon-coated silicon negative electrode material; 1000 g of the carbon-coated silicon negative electrode material is mixed with 150 g of 70Li2S·30P2S5 glassy electrolyte material, 100 g of acetylene black, 30 g of binder SBR, and 1000 mL of toluene to prepare a mixed slurry, which is coated on a copper foil, dried, and pressed into a sheet to obtain a negative electrode.
[0098] Comparative Example 3
[0099] A preparation of an all-solid-state lithium battery, which is different from Example 1 in that the second coating is directly mixed with 30g of binder SBR rubber and 1500mL of toluene to prepare a negative electrode slurry, the second coating is not heated, and the other steps remain unchanged.
[0100] Comparative Example 4
[0101] A preparation of an all-solid-state lithium battery, which is different from Example 1 in that Li 4.4 The Si material is used as the first coating and is subjected to magnetron sputtering treatment, and the other steps remain unchanged.
[0102] Comparative Example 5
[0103] A preparation of an all-solid-state lithium battery, which differs from Example 1 in that the first coating is directly mixed with 30g of binder SBR rubber and 1500mL of toluene to prepare a negative electrode slurry, and the other steps of preparing the negative electrode remain unchanged; at the same time, the LiNbO3-coated LiCoO2 positive electrode active material is changed to 1000g of TiS2 material, and the other steps remain unchanged.
[0104] Performance Testing
[0105] The all-solid-state lithium batteries obtained in the above embodiments and comparative examples were tested for battery cycle life, and the testing method was as follows: 20 all-solid-state lithium battery samples prepared in each embodiment and comparative example were taken, and each battery was subjected to a charge and discharge cycle test at a rate of 0.1C at 298±1K on a LAND CT 2001C secondary battery performance testing device.
[0106] The test steps are as follows: leave for 10 minutes; charge at constant voltage until 4.25V / 0.05C is reached; leave for 10 minutes; discharge at constant current until 3V is reached, which is one cycle. The discharge capacity of the first cycle is recorded (when TiS2 is used as the positive electrode, the upper and lower limits of the voltage are 3V / 0.05C and 1V, respectively, and the other conditions are the same). Repeat the above cycle steps. When the battery capacity is lower than 80% of the initial discharge capacity during the cycle, the cycle is terminated. The number of cycles at the end of the cycle is the cycle life of the battery. The average value is taken for each group. The results are shown in Table 1.
[0107] Table 1 Cycle life test data of each group of samples
[0108]
[0109] It can be seen from Table 1 that the discharge capacity and cycle life of Comparative Examples 1 and 3 are very poor, and the discharge capacity and cycle life of Comparative Examples 2, 4-5 are significantly lower than those of the embodiments; the battery performance of Comparative Example 1 using the carbon-coated silicon negative electrode material commonly used in lithium batteries with electrolyte is extremely poor, indicating that the negative electrode material is not suitable for all-solid-state lithium batteries; but the carbon-coated silicon negative electrode material is mixed with the solid electrolyte (Comparative Example 2), the obtained battery performance is improved compared with Comparative Example 1, but it is still far inferior to the all-solid-state lithium battery made of the negative electrode material of the embodiment of the present application; the second coating is directly used as When it is used as the negative electrode active material (Comparative Example 3), there are no ion and electron channels, and the electrochemical performance of the all-solid-state lithium battery is poor; when the lithium silicon alloy material is directly used as the negative electrode active material (Comparative Example 4), its conductivity is low and the volume expansion effect is obvious, resulting in poor electrochemical performance of the all-solid-state lithium battery; although the lithium silicon alloy is coated with carbon material (Comparative Example 5), although the conductivity is improved to a certain extent, it still has an obvious volume expansion effect and the cycle performance is poor; the all-solid-state lithium battery made using the negative electrode material of the present application has a higher negative electrode discharge specific capacity and a better battery cycle life, which is conducive to its widespread use.
[0110] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises a core and a shell arranged outside the core, a gap is formed between the core and the shell, the core comprises lithium silicon alloy particles and a first carbon material layer arranged on the surface of the lithium silicon alloy particles, the shell comprises a lithium silicon alloy layer and a second carbon material layer, the second carbon material layer is arranged between the lithium silicon alloy layer and the core, the lithium silicon alloy particles are made of Li x Si, the material of the lithium silicon alloy layer is Li y Si, wherein 0<x<4.4, 0<y≤4.
4.
2. The negative electrode material according to claim 1, characterized in that The mass ratio of the lithium silicon alloy particles to the lithium silicon alloy layer is 0.1-100.
3. The negative electrode material according to claim 1, characterized in that The total mass of the first carbon material layer and the second carbon material layer accounts for 1%-30% of the mass of the negative electrode material.
4. The negative electrode material according to claim 1, characterized in that The volume of the voids accounts for 10% to 75% of the sum of the volumes of the voids and the core.
5. The negative electrode material according to claim 1, characterized in that The particle size of the lithium-silicon alloy particles is 20nm-1μm; the thickness of the lithium-silicon alloy layer is 10nm-1μm.
6. The negative electrode material according to claim 1, characterized in that The materials of the first carbon material layer and the second carbon material layer are respectively selected from at least one of graphite, carbon black, graphene, carbon fiber, carbon nanotube and cracked carbon.
7. A method for preparing a negative electrode material, characterized in that: include: In Li z The surface of Si particles is coated with carbon material to obtain a first coating, wherein 0<z≤4.4; Coating a silicon material on the surface of the first coating to obtain a second coating; The second coating is heated to obtain a negative electrode material, wherein the negative electrode material includes a core and a shell arranged outside the core, a gap is formed between the core and the shell, the core includes lithium silicon alloy particles and a first carbon material layer arranged on the surface of the lithium silicon alloy particles, the shell includes a lithium silicon alloy layer and a second carbon material layer, the second carbon material layer is arranged between the lithium silicon alloy layer and the core, and the material of the lithium silicon alloy particles is Li x Si, the material of the lithium silicon alloy layer is Li y Si, wherein 0<x<4.4, 0<y≤4.4, x<z.
8. The preparation method according to claim 7, characterized in that: The heating includes treating at 100° C.-250° C. for 10 min-8 h.
9. An all-solid-state lithium battery, characterized in that: It comprises a positive electrode, a negative electrode and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the negative electrode comprises the negative electrode material according to any one of claims 1 to 6 or the negative electrode material prepared by the preparation method according to any one of claims 7 to 8.
10. The all-solid-state lithium battery according to claim 9, characterized in that: The negative electrode includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector, wherein the negative electrode material layer includes the negative electrode material and does not contain a solid electrolyte material and a conductive agent.
Citation Information
Patent Citations
Lithium ion battery negative electrode active material, preparation method thereof, negative electrode and lithium ion battery comprising negative electrode
CN107293701A
Carbon-coated lithium battery negative electrode material with yolk-eggshell structure and preparation method
CN111952549A